Current status and prospects of minimally invasive hepatobiliary surgery - Jie Li; Ping Chen (Intelligent Surgery)
In recent years, minimally invasive surgery has developed rapidly and has become an important means of treating hepatobiliary diseases. The development of minimally invasive surgery includes advancements in surgical instruments, laparoscopic equipment, surgical techniques, and related theories. Currently, most traditional hepatobiliary surgeries can be performed using laparoscopic methods. Minimally invasive surgery is the direction for future surgical development, with goals of becoming more intelligent, compact, and multifunctional. In the future, the continuous integration of artificial intelligence, robotic technology, virtual reality and augmented reality technologies, and remote technologies with medicine will further promote the development of minimally invasive surgery. This article provides a brief overview of the current status and prospects of minimally invasive surgery.